Informatics Approaches to Functional MRI Odor Mapping of the Rodent Olfactory Bulb: OdorMapBuilder and OdorMapDB - Liu, Nian; Xu, Fuqiang; Marenco, Luis; Hyder, Fahmeed; Miller, Perry; Shepherd, Gordon M. (Neuroinformatics (Totowa, N.J.), 2004)
The present study applies informatics tools to aid and extend fMRI analysis of the coding mechanism of neural signals in the rodent olfactory system. Odor stimulation evokes unique spatial patterns of activity in the glomerular layer of the mammalian olfactory bulb (OB). An open-source software program, OdorMap-Builder, has been developed to process the high resolution anatomical and functional MRI images of the OB and to generate single two-dimensional flat maps, called odor maps, that describe the spatial activity patterns in the entire glomerular layer. Odor maps help identify the spatial activity patterns from the tremendous amount of fMRI data and they serve as ideal representation of space coding for the olfactory signals in the OB in response to a given odor stimulation. Based on the fMRI technology, OdorMapBuilder provides comparable odor maps on the intra-subject basis, a significant step towards the detailed analyses of the effects of odor types and/or concentrations. In addition, a new database, OdorMapDB, is developed to provide a repository for the generated odor maps. Web interfaces to the database are provided for the data entry, modification and retrieval. OdorMapDB is based on the EAV/CR (entity-attribute-value with classes and relationships) architecture and it is integrated with two other SenseLab olfactory databases: the olfactory receptor and odor databases. Both OdorMapBuilder and OdorMapDB should serve as useful tools and resources for the field and help facilitate experimental research in understanding the olfactory system and the mechanism for smell perception.